2017
DOI: 10.1016/j.vetmic.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Use of signature-tagged mutagenesis to identify genes associated with colonization of sheep by E. coli O157:H7

Abstract: Outbreaks of Escherichia coli O157:H7 in the United States due to contaminated foods are a public health issue and a continuing problem. The major reservoir for these organisms is the gastrointestinal tract of ruminants where they are a member of the resident microbiota. Several factors that contribute to the colonization of cattle have been identified, but a systematic screen of genes that might contribute to the colonization and persistence phenotype in mature ruminants has not been reported. Using a sheep m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example, a TnSeq experiment of Snodgrassella alvi colonization in honey bees also revealed that LPS is an important factor in colonization ( Powell et al 2016 ). In non-insect hosts, E. coli LPS mutants are hyper-susceptible to host immunity in C. elegans (( Kuo et al 2016 )), and LPS is important for E. coli colonization and persistence in sheep ( Cornick et al 2017 ). Vibrio cholerae LPS mutants had a 30 fold reduction in colonization of the mouse gut ( Nesper et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a TnSeq experiment of Snodgrassella alvi colonization in honey bees also revealed that LPS is an important factor in colonization ( Powell et al 2016 ). In non-insect hosts, E. coli LPS mutants are hyper-susceptible to host immunity in C. elegans (( Kuo et al 2016 )), and LPS is important for E. coli colonization and persistence in sheep ( Cornick et al 2017 ). Vibrio cholerae LPS mutants had a 30 fold reduction in colonization of the mouse gut ( Nesper et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Glu 253 residue, together with Tyr 219 were identified in a previous study as essential for enzymatic activity and virulence function of NleB1 [152]. Interestingly, the presence of nleB1 in EHEC and EPEC strains is associated with colonization of sheep [153] and cattle [154], with human disease [155][156][157][158][159], and with an increase in disease severity [160][161][162][163][164][165]. In contrast, the role of NleB2 in virulence is currently unclear.…”
Section: Role In Virulencementioning
confidence: 98%